Incidence, Distribution, and Cost of Lawn-Mower Injuries in the United States, 2006-2013. (September 2018) - Hottinger, Daniel G.; Nasr, Isam; Canner, Joseph K.; Kattail, Deepa; Koka, Rahul; Schwengel, Deborah
Objectives: Characterization of the epidemiology and cost of lawn-mower injuries is potentially useful to inform injury prevention and health policy efforts. We examined the incidence, distribution, types and severity, and emergency department (ED) and hospitalization charges of lawn-mower injuries among all age groups across the United States. Methods: This retrospective, cross-sectional study used nationally representative, population-based (all-payer) data from the US Nationwide Emergency Department Sample for lawn-mower–related ED visits and hospitalizations from January 1, 2006, through December 31, 2013. Lawn-mower injuries were identified by using International Classification of Diseases, Ninth Revision, Clinical Modification code E920 (accidents caused by a powered lawn mower). We analyzed data on demographic characteristics, age, geographic distribution, type of injury, injury severity, and hospital charges. Results: We calculated a weighted estimate of 51 151 lawn-mower injuries during the 8-year study period. The most common types of injuries were lacerations (n = 23 907, 46.7%), fractures (n = 11 433, 22.4%), and amputations (n = 11 013, 21.5%). The most common injury locations were wrist or hand (n = 33 477, 65.4%) and foot or toe (n = 10 122, 19.8%). Mean ED charges were 2482 per patient, and mean inpatient charges were 36 987 per patient. The most common procedures performed were wound irrigation or debridement (n = 1436, 29.9%) and amputation (n = 1230, 25.6%). Conclusions: Lawn-mower injuries occurred at a constant rate during the study period. Changes to nationwide industry safety standards are needed to reduce the frequency and severity of these preventable injuries.